2006
DOI: 10.1159/000090201
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnoea-Hypopnoea Index Is an Independent Predictor of High-Sensitivity C-Reactive Protein Elevation

Abstract: Background: Recent reports have identified the apnoea and hypopnoea index (AHI) as an additional independent risk factor for cardiovascular morbidity and mortality. However, several studies reported contradictory results about the association between the serum C-reactive protein (CRP) level and the severity of apnoea. Objective: The purpose of this work is to study this association in patients referred to the sleep laboratory for clinical suspicion of sleep apnoea and presenting a wide range of AHI. Methods: F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
0
32
0
3
Order By: Relevance
“…The pathophysiological changes in OSA can activate peripheral neutrophils and monocytes, leading to enhanced generation of cytokines [4, 8], resulting in the elevated levels of pro-inflammatory mediators [2,3,4,5,6,7]. Nocturnal hypoxia has emerged as a primary candidate to enhance inflammatory cascades in OSA [1, 6, 12, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological changes in OSA can activate peripheral neutrophils and monocytes, leading to enhanced generation of cytokines [4, 8], resulting in the elevated levels of pro-inflammatory mediators [2,3,4,5,6,7]. Nocturnal hypoxia has emerged as a primary candidate to enhance inflammatory cascades in OSA [1, 6, 12, 41].…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of pro-inflammatory mediators are elevated in the circulation of patients with OSA [2,3,4,5,6,7]. Additionally, OSA patients have peripheral leukocytes which can generate larger amounts of cytokines [4, 8], adhesion molecules [9] and free radicals [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the deleterious consequences of OSAHS are a result of frequent episodes of hypoxemia that occur during the night [40]. Even though the pathophysiology of cardiovascular complications is multifactorial, involving sympathetic excitation, endothelial dysfunction, inflammation and insulin resistance, it is probable that intermittent episodes of hypoxia and, particularly, intermittent episodes of re-oxygenation play a central role in the process [41,42,43,44]. If so, the prevention of hypoxemia episodes and re-oxygenation in OSAHS could result in the prevention of inflammatory activation, and, thereby, this treatment facilitates, at least in part, a reduction in cardiovascular risks [40].…”
Section: Discussionmentioning
confidence: 99%
“…Boudjeltia et al [15] observed an independent association between the AHI and hsCRP in 49 patients referred to the sleep laboratory for suspected sleep apnea. In multivariate analysis, including age, BMI, gender, hypertension, diabetes, tobacco, microarousal index, AHI, total cholesterol, triglycerides and LDL cholesterol, AHI was the only variable independently associated with hsCRP.…”
Section: Discussionmentioning
confidence: 99%